(L)-type activation functions in a system of ordinary differential equations. Issue 8 (17th November 2018) - Tatar, Nasser-Eddine
Abstract: Activation functions of (L)-type are considered in a problem arising in Neural Network Theory. We prove an exponential stabilization result for these nonlinear functions which do not satisfy necessarily the commonly assumed conditions in the previous works. We also consider the special case of constant coefficients and a control problem.